A Renaissance of Agri-(Culture): An investigation into peri-urban agriculture as a catalyst for sustainable development through the integration of human behavious, natural processes and technology - Crafford, Abre (University of Pretoria, 2021)
Mini Dissertation (MArch Prof)--University of Pretoria, 2020.